Stability of dipolar bosons in a quasiperiodic potential - Paolo Molignini; Barnali Chakrabarti (Physical Review Research)
Quasiperiodic potentials and dipolar interactions each impose long-range order in quantum systems, but their interplay unlocks a rich landscape of unexplored quantum phases. In this work, we investigate how dipolar bosonic crystals respond to correlated disorder in the form of quasiperiodic potentials. Using exact numerical simulations and a suite of observables—including order parameters, energy, density distributions, and two-body coherence measures—we explore one-dimensional dipolar bosons in quasiperiodic lattices at both commensurate and incommensurate fillings. Our results reveal a complex competition between superfluid, Mott-insulator, density-wave, and crystalline phases, governed by the intricate balance of dipolar interactions, kinetic energy, and disorder strength. Crucially, we identify mechanisms that influence dipolar crystals, showing their surprising robustness even in the presence of strong quasiperiodic disorder. Strikingly, we challenge previous claims by demonstrating that a kinetic crystal phase—expected to precede full crystallization—does not emerge in the ground state. Instead, its traits appear only under moderate disorder, but never fully develop, giving way to a direct transition from a charge density wave to a crystal state. These findings provide new insights into the resilience of many-body quantum phases in complex environments and pave the way for engineering exotic quantum states in ultracold atomic systems.